Prediction of Srebp-1 as a Key Target of Qing Gan San Against MAFLD in Rats via RNA-Sequencing Profile Analysis - Yang, Bendong; Sun, Jingyue; Liang, Shufei; Wu, Peixuan; Lv, Rui; He, Yanping; Li, Deqi; Sun, Wenlong; Song, Xinhua (Frontiers in Pharmacology, 2021)
Metabolism-associated fatty liver disease (MAFLD) is the most common chronic liver disease worldwide, and the use of traditional Chinese medicines (TCMs) to treat this disease has attracted increasing attention. The Qing Gan San (QGS) formula comprises Polygonatum sibiricum, the peel of Citrus reticulata Blanco, the leaves of Morus alba L, Cichorium intybus, Glycyrrhiza uralensis Fisch, and Cirsium setosum. The present study aimed to uncover the anti-hyperlipidaemic effects, hepatic fat accumulation-lowering effects and mechanisms of QGS in high-fat diet-induced MAFLD rats. QGS significantly reduced the levels of total cholesterol and triglycerides in both serum and liver tissue and partially protected hepatic function. Additionally, QGS significantly ameliorated hepatic lipid accumulation with histopathology observation, as demonstrated by H&E and oil red O staining. RNA sequencing was used to further investigate the key genes involved in the development and treatment of MAFLD. Hierarchical clustering analysis showed that the gene expression profiles in rats with MAFLD were reversed to normal after QGS treatment. QGS had 222 potential therapeutic targets associated with MAFLD. Enrichment analysis among these targets revealed that QGS affected biological functions/pathways such as the regulation of lipid metabolic processes (GO: 0019216) and the non-alcoholic fatty liver disease pathway (hsa04932), and identified Srebp-1 as a key regulator in the synthesis of cholesterol and triglycerides. Subsequently, both immunofluorescence and Western blot analyses demonstrated that QGS suppressed the transfer of Srebp-1 to the nucleus from the cytoplasm, suggesting that the activation of Srebp-1 was inhibited. Our study reveals the effects and mechanisms of QGS in the treatment of MAFLD and provides insights and prospects to further explore the pathogenesis of MAFLD and TCM therapies.